Ultralow switching voltage slope based on two-dimensional materials for integrated memory and neuromorphic applications. (March 2020) - Sun, Linfeng; Hwang, Genuwoo; Choi, Wooseon; Han, Gyeongtak; Zhang, Yishu; Jiang, Jinbao; Zheng, Shoujun; Watanabe, Kenji; Taniguchi, Takashi; Zhao, Mali; Zhao, Rong; Kim, Young-Min; et al.
Abstract: To realize ultrafast and energy-efficient electronic devices, reducing the switching voltage slope for ON and OFF states that scales the supply voltage and device dimensions is critical. Novel device architectures based on two-dimensional (2D) materials have overcome the fundamental thermionic limit of the switching slope (60 mV/dec); however, a versatile switching device required for highly integrated memory and neuromorphic applications has not been achieved with such exceptional switching slope characteristics. Here, we demonstrate a switching voltage slope down to 0.62 mV/dec in a threshold switching device based on a vertical heterojunction of silver/hexagonal boron nitride (h-BN)/graphene. The sub-1 mV/dec switching slope for the first time, maintaining a high ON/OFF ratio (up to 10 10 ), originates from the unique coupling between the migrated silver atoms and the chemically-inert graphene electrode through the 2D insulating h-BN. Moreover, our original switching device enables the evolution from a conventional volatile (threshold switching) to non-volatile memristive state by adequate voltage spikes, which is ideal for selector applications in highly integrated crossbar array architecture and in a novel synaptic device for neuromorphic computing. Graphical abstract: Ultralow (down to sub-1 mV/dec) switching voltage slopes maintaining extraordinary ON/OFF ratios beyond 10 10 could be realized by using a van der Waals heterostructure, which provides an ideal component for crossbar array architecture and novel synaptic devices for neuromorphic computing. Image 1 Highlights: A switching device based on a vertical heterojunction was realized with sub-1 mV/dec switching voltage slope. The resistance switching ratio of our tunable memory cell reaches up to 10 11 . Scanning transmission electron microscopy reveals a unique switching mechanism of our device. The reliable memory switching transitions from volatile to non-volatile memory emulates biological synaptic operations.